A FeS2 modified hierarchical porous carbon electrochemical sensor and its preparation method and application
Through the combination of nano-FeS2 modified graded porous carbon materials and glass carbon electrodes, a low-cost electrochemical sensor with simple preparation process is formed, solving the high cost and complex preparation problems of detecting HX, XT and UA in the prior art. , realizes detection effects with high sensitivity and wide linear range.
Patent Information
- Application Number
- CN202210924181.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-03
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2042-08-03
AI Technical Summary
Some electrochemical sensors used in the prior art for detecting hypoxanthine (HX), xanthine (XT) and uric acid (UA) have problems such as high cost, complex preparation process, and narrow linear range, which are difficult to meet low cost and simple preparation. , high sensitivity, low detection limit and wide linear range requirements.
The nano-FeS2 modified graded porous carbon material is used as the modified layer of the electrochemical sensor. The material is prepared by hydrothermal reaction and calcination, and combined with the glass carbon electrode to form the FeS2 modified graded porous carbon electrochemical sensor.
Selective or simultaneous detection of HX, XT and UA is achieved, with high sensitivity, strong selectivity and good stability, and the detection limits are 0.047μM, 0.21μM and 0.069μM respectively, which are suitable for the detection of actual samples.
Smart Images

Figure CN115290726B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrochemical sensors, and in particular relates to a FeS2 modified hierarchical porous carbon electrochemical sensor and a preparation method and application thereof. Background Art
[0002] Hypoxanthine (HX), xanthine (XT) and uric acid (UA) in the human body are metabolites of adenosine triphosphate (ATP) (Ojani R, Alinezhad A, Abedi Z. A highly sensitive electrochemical sensor for simultaneous detection of uric acid, xanthine and hypoxanthine based on poly(l-methionine) modified glassy carbon electrode[J]. Sensors and Actuators B: Chemical, 2013, 188: 621-630). The metabolic process is as follows: adenosine triphosphate is degraded into adenosine diphosphate, adenosine diphosphate is degraded into adenosine monophosphate, adenosine monophosphate is finally degraded into inosine, inosine is degraded into HX, HX is converted into XT under the action of xanthine oxidase, and XT is finally converted into UA under the action of xanthine oxidase (Pierini GD, Robledo SN, Zon MA, et al. Development of an electroanalytical method to control quality in fish samples based on an edge plane pyrolytic graphite electrode. Simultaneous determination of hypoxanthine, xanthine and uric acid[J]. Microchemical Journal, 2018, 138: 58-64). The three purine metabolites exist simultaneously in human body fluids, and the concentration of metabolites can be used as a sensitive indicator of many clinical diseases, such as xanthinuria, gout, hyperuricemia, renal failure, etc. (Odewunmi NA, Kawde AN, Ibrahim M. ElectrochemicallyInspired Copper (II) Complex on Disposable Graphite Pencil Electrode forEffective Simultaneous Detection of Hypoxanthine, Xanthine, and Uric Acid[J].Electroanalysis, 2018, 30 (10): 2311-2320). The determination of HX, XT and UA is of great significance in clinical medicine, biochemistry and food (Ibrahim H, Temerk Y. A novel electrochemical sensorbased on B doped CeO2 nanocubes modified glassy carbon microspheres pasteelectrode for individual and simultaneous determination of xanthine andhypoxanthine[J]. Sensors and Actuators B: Chemical, 2016, 232: 125-137). Therefore, it is necessary to develop a method that can selectively or simultaneously detect these three ATP metabolites. At present, the main determination methods include high performance liquid chromatography (HPLC), UV-visible spectrophotometry, capillary electrophoresis and electrochemical detection methods. Among them, the electrochemical method has the advantages of low cost, fast detection speed, high sensitivity, strong selectivity and simple operation (Luo A, Lian QW, An ZZ, et al. Simultaneous determination of uric acid, xanthineand hypoxanthine based on sulfonic groups functionalized nitrogen-dopedgraphene[J]. Journal of Electroanalytical Chemistry, 2015, 756: 22-29). Many researchers have used electrochemical sensors to selectively or simultaneously detect HX, XT and UA. In 1978, Toshio Yao et al. (Toshio Y, Yoichi T, Tamotsu W, et al. Anodic Voltammetry and its AnalyticalApplication to the Detection and Simultaneous Determination of Hypoxanthine,Xanthine, and Uric acid[J].BULLETIN OF THE CHEMICAL SOCIETY OF JAPAN, 1978, 51 (10): 2937-2941) For the first time, HX, XT and UA were simultaneously determined by glassy carbon electrode (GCE), but no linear relationship between the concentration of the detected substance and the response current was made. Since this system used an unmodified glassy carbon electrode, the response current was small. Later, researchers used aminohydroxynaphthalene sulfonic acid (Mathew MR, Kumar K G. Poly (Amino HydroxyNaphthalene Sulphonic Acid) Modified Glassy Carbon Electrode; An EffectiveSensing Platform for the Simultaneous Determination of Xanthine andHypoxanthine[J]. Journal of The Electrochemical Society, 2020, 167 (4):047519), -NaFeO2 (Durai L, Badhulika S. Facile synthesis of large area pebble-like β-NaFeO2 perovskite for simultaneous sensing of dopamine, uric acid, xanthine and hypoxanthine in human blood[J]. Materials Science and Engineering: C, 2020, 109:110631), Co-CeO2 (Lavanya N, Sekar C, Murugan R, etal. An ultrasensitive electrochemical sensor for simultaneous determinationof xanthine, hypoxanthine and uric acid based on Co doped CeO2 nanoparticles[J]. Materials science & engineering: C, 2016, 65 (3): 278-286) and gold-modified carbon nanotubes (Sen S, Sarkar P.A simple electrochemical approach to fabricatefunctionalized MWCNT-nanogold decorated PEDOT nanohybrid for simultaneousquantification of uric acid, xanthine and hypoxanthine[J]. Anal Chim Acta,2020, 1114: 15-28) and other materials to modify glassy carbon electrodes for selective or simultaneous detection of HX, XT and UA. However, these sensors have some defects, such as high cost, complex preparation process, narrow linear range, etc. Therefore, it is urgent to prepare an electrochemical sensor with low cost, simple preparation process, high sensitivity, low detection limit and wide linear range for selective or simultaneous detection of these biological small molecules. . Summary of the invention
[0003] The present invention aims to solve the problems of lack of modification materials for determination of HX, XT and UA, high cost, complicated manufacturing process, narrow linear range, etc., expands the utilization of porous carbon sensors, and invents a nano-FeS2 modified graded porous carbon electrochemical sensor for selectively or simultaneously detecting three ATP metabolites and a preparation method thereof; in the present invention, the carbon source is low in price, the preparation method of the modification material is simple in process, the operation is highly feasible and simple, and the electrochemical performance is efficient and sensitive, which is suitable for the promotion of electrochemical sensors.
[0004] To achieve the above object, the technical solution adopted by the present invention is as follows:
[0005] A FeS2-modified hierarchical porous carbon electrochemical sensor, wherein the hierarchical porous carbon electrochemical sensor is an electrode modified with FeS2 and hierarchical porous carbon.
[0006] Based on a general inventive concept, another object of the present invention is to provide a method for preparing the above-mentioned FeS2 modified hierarchical porous carbon electrochemical sensor, comprising the following steps:
[0007] (1) Preparation of FeS2-modified hierarchical porous carbon materials
[0008] The inner pulp of orange peel is used as carbon source, 98% H2SO4 is used as sulfur source, SiO2 colloid is used as silicon source, and FeCl3 is introduced as activator. After being uniformly mixed with ultrapure water, a hydrothermal reaction is carried out.
[0009] The gel after the hydrothermal reaction was dried, calcined in a tube furnace under the protection of inert gas, etched three times with HF, and then repeatedly washed with water and ammonia until neutral, to obtain a FeS2-modified hierarchical porous carbon material;
[0010] (2) Preparation of FeS2-modified hierarchical porous carbon-modified electrodes
[0011] The FeS2-modified hierarchical porous carbon material prepared in step (1) is mixed with ultrapure water, and after ultrasonic dispersion, a suspension is formed. The suspension is drop-coated on a glassy carbon electrode and dried to obtain a FeS2-modified hierarchical porous carbon-modified electrode, and electrochemical detection is performed in a phosphate buffer solution.
[0012] Preferably, in step (1), the amount ratio of the orange peel pulp, 98% H2SO4, SiO2 colloid and FeCl3 is 1g~5g: 0.5ml~1.5ml: 3ml~7ml: 1g~2g: 20ml~50ml.
[0013] Preferably, in step (1), the temperature of the hydrothermal reaction is 160° C. to 200° C., and the time is 3 h to 5 h.
[0014] Preferably, in step (1), the calcination temperature in the tubular furnace is 800° C. to 1000° C., the heating rate is 3.75° C. / min, and the calcination time is 3.5 h to 4.5 h.
[0015] Preferably, in step (2), the inert gas is N2 and the concentration of HF is 10%wt.
[0016] Preferably, in step (2), the ratio of FeS2-modified hierarchical porous carbon material to ultrapure water is 1 mg / mL, and the amount of the suspension applied on the glassy carbon electrode is 5 μL.
[0017] Preferably, in step (2), the prepared FeS2-modified hierarchical porous carbon-modified electrode is used as the working electrode, the platinum wire electrode is used as the counter electrode, and the reference electrode is a saturated calomel electrode to form a three-electrode system, and a phosphate buffer solution is used as the electrolyte solution, and the content of XT, HX, and UA in the test solution is detected by differential pulse voltammetry.
[0018] Preferably, in step (2), the pH of the phosphate buffer solution is 2 and the concentration is 0.1 mol / L.
[0019] Based on a general inventive concept, another object of the present invention is to protect the application of the above-mentioned FeS2 modified hierarchical porous carbon electrochemical sensor in the selective or simultaneous detection of three ATP metabolites.
[0020] Compared with the prior art, the preparation method of the nano-FeS2 modified hierarchical porous carbon electrochemical sensor for selectively or simultaneously detecting three ATP metabolites of the present invention has the following advantages:
[0021] The carbon source adopted by the present invention is waste biomass, which is renewable and realizes the recycling of waste resources. At the same time, it has the characteristics of simple preparation process, easy operation and low cost.
[0022] 2. The electrochemical sensor prepared by the present invention can selectively or simultaneously effectively detect the contents of XT, HX, and UA, and has the characteristics of high sensitivity (the detection limits (LODs) of XT, HX, and UA are 0.047 μM, 0.21 μM, and 0.069 μM (S / N=3) respectively), strong selectivity, and good stability. Finally, the prepared modified electrode can also be used for actual sample detection of the three ATP metabolites in fetal bovine serum samples.
[0023] 3. The electrochemical sensor prepared by the present invention has oxidase-like characteristics during determination, which increases the detection range and is superior to the linear relationship of the traditional modified electrode. At the same time, the modified electrode can effectively catalyze the oxidation of 3,3′,5,5′-tetramethylbenzylamine (TMB, a typical peroxidase substrate) by hydrogen peroxide or directly oxidize TMB, showing the dual enzyme characteristics of peroxidase and oxidase. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Supplementary explanation: By changing the metal source (FeCl3, CoCl2, NiCl2, CuCl2, ZnCl2), the prepared modified electrodes are named: FeS2 / PCMs / GCE, Co9S8 / PCMs / GCE, Ni3S2 / PCMs / GCE, Cu2S / PCMs / GCE, ZnS / PCMs / GCE, PCMs / GCE without metal source, and the bare electrode is PCMs.
[0025] Figure 1 In 5 mM [Fe(CN)6] 3− / 4− Electrochemical impedance spectroscopy (CV) (A) and cyclic voltammetry (B) curves of FeS2 / PCMs / GCE (a), Co9S8 / PCMs / GCE (b), Ni3S2 / PCMs / GCE (c), Cu2S / PCMs / GCE (d), ZnS / PCMs / GCE (e), PCMs / GCE (f) and bare electrode (g) in solution.
[0026] Figure 2 Electrode stability of FeS2 / PCMs / GCE (A), Co9S8 / PCMs / GCE (B), Ni3S2 / PCMs / GCE (C), Cu2S / PCMs / GCE (D) and ZnS / PCMs / GCE (E).
[0027] Figure 3Differential pulse voltammograms (DPV) of FeS2 / PCMs / GCE (a), Co9S8 / PCMs / GCE (b), Ni3S2 / PCMs / GCE (c), Cu2S / PCMs / GCE (d), ZnS / PCMs / GCE (e), PCMs / GCE (f) and bare electrode (g) in PBS (pH = 2.0) containing UA (60 μM), XT (60 μM) and HX (60 μM).
[0028] Figure 4 CV graphs of FeS2 / PCMs / GCE for UA (60μM), HX (60μM) and XT (60μM) at different scan rates (25mV / s, 50mV / s, 75mV / s, 100mV / s, 200mV / s, 300mV / s, 400mV / s and 500mV / s) (A), and the relationship between the oxidation peak current and the scan rate (B), and the oxidation peak current and the square root of the scan rate (C); The peak potential of the oxidation peaks of UA, HX and XT ( E p,a )and lnv relationship (D).
[0029] Figure 5 DPV diagrams of FeS2 / PCMs / GCE for UA (60μM), XT (60μM) and HX (60μM) at different pH (pH=1, 2, 3, 4, 5, 6 and 7) (A); Relationship between the oxidation peak current (B), potential difference (C) and potential (D) of UA, XT and HX and pH.
[0030] Figure 6 DPV responses of (A) UA (0.3-500μM), (C) XT (0.3-500μM) and (E) HX (0.7-700μM) on FeS2 / PCMs / GCE at different concentration levels; (B) Relationship between the concentration of UA (0.3-200μM) and (F) HX (0.7-200μM) and the response current; (D) Relationship between the inverse of the concentration of XT (0.3-500μM) and the inverse of the response current, inset: relationship between concentration and response current.
[0031] Figure 7DPV graph of FeS2 / PCMs / GCE in the presence of different concentrations of UA (0.5-1000μM) and HX (20μM) and XT (20μM) (A), linear relationship between UA concentration (0.5-200μM) and response current in the low concentration range, inset: relationship curve between UA concentration (0.5-1000μM) and response current (B); DPV graph of FeS2 / PCMs / GCE in the presence of different concentrations of XT (0.1-500μM) and UA (30μM) and HX (20μM) (C), Linear relationship between XT concentration (0.1-100μM) and response current in the low concentration range, inset: relationship curve between XT concentration (0.1-500μM) and response current (D); DPV diagram of FeS2 / PCMs / GCE containing different concentrations of HX (0.7-700μM) and in the presence of UA (30μM) and XT (20μM) (E), Linear relationship between HX concentration (0.7-200μM) and response current in the low concentration range, inset: relationship curve between XT concentration (0.7-700μM) and response current (F).
[0032] Figure 8 DPV responses of different concentrations of UA (5-600μM), XT (0.3-600μM) and HX (2-600μM) on FeS2 / PCMs / GCE (A), and the relationship curve between the response current and concentration (B); the relationship between the concentration of UA (5-90μM) and XT (0.3-60μM) in the low concentration range and the response current (C, E); the relationship between the reciprocal of the concentration of the low concentration range and HX (2-70μM) and the reciprocal of the response current, inset: the relationship between the concentration of HX (2-70μM) and the response current (D).
[0033] Fig. 9 UV-resolution breadth scans of different systems (A and B) and different materials (C), with insets corresponding to the relevant photographs.
[0034] Fig.10 The stability (A), reproducibility (B) and anti-interference ability (a: blank, b: potassium ion, c: sodium ion, d: ammonium ion, e: chloride ion, f: nitrate ion, g: sucrose, h: glucose, i: fructose, j: ascorbic acid, k: L-glutamic acid, l: D-leucine) (C) of FeS2 / PCMs / GCE in PBS with pH 2.0 containing 60 μM UA, XT and HX. DETAILED DESCRIPTION
[0035] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in conjunction with specific embodiments, but the present invention is not limited to these embodiments. It should be noted that, under the premise of not conflicting, the embodiments described below or the technical features can be arbitrarily combined to form new embodiments. In the present invention, unless otherwise specified, all parts and percentages are mass units, and the equipment and raw materials used can be purchased from the market or are commonly used in the art. The methods in the following embodiments, if not otherwise specified, are conventional methods in the art.
[0036] As used herein, the terms "comprises," "including," "contains," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0037] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range limited by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including a range of "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5" etc. When a numerical range is described in this article, unless otherwise specified, the range is intended to include its end values and all integers and fractions within the range.
[0038] The specific embodiments of the present invention are described in detail below with reference to the accompanying drawings.
[0039] Example 1
[0040] Collect discarded orange peels, wash them, take 1g of the inner pulp, chop it and put it into a polytetrafluoroethylene reactor, add 1mL H2SO4, 2g FeCl3, 5mL SiO2 colloid into 30mL water, and add 30ml ultrapure water to the polytetrafluoroethylene reactor after mixing evenly, and add it into the polytetrafluoroethylene reactor, hydroheat at 453K for 12h, and dry the hydrothermal gel;
[0041] Under nitrogen protection, the dried gel was calcined in a tube furnace at 1173K for 4h (heating rate: 2K / min), the calcined material was etched three times with 10% HF, and then repeatedly washed with water and ammonia until neutral (pH=7.0), obtaining FeS2-modified biomass-grade porous carbon material;
[0042] Weigh 1 mg of the above-mentioned porous carbon material and disperse it in 1 mL of ultrapure water. Ultrasonicate for 10 minutes to form a uniformly dispersed and stable mixed solution. Take 5 μL of the mixed solution and drop it on the surface of the glassy carbon electrode, then dry it in an infrared drying oven to obtain a porous carbon microsphere modified electrode FeS2 / PCMs / GCE.
[0043] The electrochemical performance of the porous carbon modified electrode (FeS2 / PCMs / GCE) was tested: Figure 1 From A, we can see that the EIS curve of the PCMs / GCE electrode is a slanted line, and there is almost no arc at high frequencies. Figure 1 The potential difference in B is smaller than that of the bare electrode, which shows that the modified material has good electron conductivity.
[0044] Figure 2 In order to study the electrochemical cycling stability of the unmodified material, 5 mM [Fe(CN)6] 3- / 4- The cyclic voltammetry scans were performed continuously for 100 times in the solution, and the CV graph of FeS2 / PCMs / GCE after 100 cycles showed almost no change. I p,a and I p,c The relative standard deviations (RSD) values were 0.31%, 0.17%, 0.70%, and 0.79%, respectively, indicating that FeS2 / PCMs / GCE and ZnS / PCMs / GCE have good electrochemical cycling stability and electrode stability.
[0045] Electrochemical sensing detection is performed on the porous carbon modified electrode (FeS2 / PCMs / GCE) under the test object: Figure 3 In the figure, the response current of the sensor prepared by the modified electrode to UA, XT, and HX in 0.1M PBS (pH=2.0) is shown. It is found that FeS2 / PCMs / GCE has the highest response current, and the peak potentials of the oxidation peaks of UA, XT, and HX are 0.57, 0.92, and 1.28, respectively, with a large potential difference, indicating that FeS2 / PCMs can be used to selectively and simultaneously detect these three molecules.
[0046] The parameters of the porous carbon modified electrode (FeS2 / PCMs / GCE) were optimized as follows: Figure 4 A Cyclic voltammetry curves at different scan rates. All CV curves have similar shapes, indicating that FeS2 / PCMs has good reaction kinetics and reaction stability. Figure 4 B I p,a and v are not linearly related, but the oxidation peak current ( I p,a ) and the square root of the scan rate (v 1 / 2 ) is proportional to ( Figure 4 C), related peak potential ( E p,a ) and the logarithm of the scan rate ( lnv ) is linearly related.
[0047] Figure 5 The effect of different pH on the oxidation peak current ( I p,a ) and oxidation peak potential ( E p,a ) and Figure 5 B shows that the response current is the largest when the pH is 2; Figure 5 D can be known E p,a It has a linear relationship with pH.
[0048] Nanozyme properties of the above porous carbon modified electrode (FeS2 / PCMs / GCE):
[0049] like Figure 6 In D, when the concentration of XT is low, the oxidation peak current of XT shows a good linear relationship with the concentration, but when the concentration continues to increase, the oxidation peak current gradually deviates from the linear trend. In addition, we can also find that the reciprocal of the oxidation peak current of XT ( 1 / I ) and the inverse of the concentration ( 1 / C ) showed a good linear relationship, which indicated that FeS2 / PCMs had the nanozyme properties for electrocatalytic oxidation of XT; Figure 6 As shown in A, B and E, F, the response current reaches saturation with the increase of UA and HX concentration, but does not meet the response characteristics of oxidase-like enzymes. Therefore, FeS2 / PCMs / GCE does not have the nanozyme characteristics of electrocatalytic oxidation of UA and HX, and is a non-enzymatic detection of UA and HX.
[0050] Figure 7 In 0.1M PBS (pH=2.0), the concentration of two analytes was kept constant and the concentration of another analyte was changed for detection. It can be clearly found that when UA and HX coexisted, there was no obvious interference with the detection of XT. The reciprocal of the peak current of XT oxidation in the low concentration range ( 1 / I ) and the inverse of the concentration ( 1 / C ) shows a good linear relationship, indicating that it also has oxidase-like characteristics ( Figure 7 C, Figure 7 D). When the concentrations of HX and XT were uniformly 20 μM, the response current of UA showed a good linear relationship with the concentration in the range of 0.5-200 μM ( Figure 7 A, Figure 7B). When the concentrations of UA and XT were controlled at 30 μM and 20 μM, respectively, the response current of HX showed a good linear relationship with the concentration in the range of 0.7-200 μM ( Figure 7 E, Figure 7 F). However, like the individual tests, FeS2 / PCMs / GCE did not have oxidase-like characteristics when detecting UA and HX.
[0051] Figure 8 For the simultaneous detection of UA, HX and XT by FeS2 / PCMs / GCE, the peak current response of the three analytes changing simultaneously was studied by DPV method. Figure 8 A, when the analyte concentration increases from 0.3 μM to 700 μM, the response current first increases linearly with the concentration, then slowly deviates from the linearity and tends to be stable ( Figure 8 B); FeS2 / PCMs / GCE still has oxidase-like characteristics when detecting XT ( Figure 8 D), but only non-enzymatic detection is available for UA and HX ( Figure 8 C, Figure 8 E). The slopes of the linear equations for UA and HX when tested alone and the slope of the linear equation for low concentration of XT were evaluated ( Figure 6 B, Figure 6 D, Figure 6 F), the minimum detection limits (LOD) of FeS2 / PCMs / GCE for the three analytes were calculated, which were 0.069μM, 0.047μM and 0.21μM, respectively. This result shows that FeS2 / PCMs / GCE has a good detection effect on UA, XT and HX, and can be used as a new sensor for simultaneous or selective detection of the three analytes, and can also be used as a new nanozyme sensor for the detection of XT alone.
[0052] Fig. 9 In order to verify the catalytic potential of various enzymes of FeS2 / PCMs, such as Fig. 9 As shown in A, the prepared FeS2 / PCMs can effectively catalyze the oxidation of 3,3′,5,5′-tetramethylbenzylamine (TMB, a typical peroxidase substrate) by hydrogen peroxide, producing a strong blue signal. Fig. 9 A strong absorption peak was observed in A (i.e., the maximum absorbance of oxidized TMB was 652 nm), indicating that FeS2 / PCMs has good peroxidase catalytic activity. Moreover, FeS2 / PCMs can directly oxidize TMB to produce a blue signal in the absence of H2O2 ( Fig. 9 B), indicating the oxidase catalytic activity of FeS2 / PCMs.
[0053] like Fig. 9As shown in Figure C, compared with other materials, the absorption peak of FeS2 / PCMs is the largest, indicating that the peroxidase activity of FeS2 / PCMs is the highest. The above shows that FeS2 / PCMs has the dual enzyme properties of peroxidase and oxidase.
[0054] Repeatability, reproducibility, anti-interference ability and actual sample analysis of the above porous carbon modified electrode (FeS2 / PCMs / GCE): Fig.10 As can be seen in A, different substances have no obvious interference in the detection of the three analytes, which indicates that FeS2 / PCMs / GCE has strong anti-interference ability.
[0055] In repeatability and reproducibility experiments ( Fig.10 B. Fig.10 C), all three analytes had low RSD values, indicating that the FeS2 / PCMs / GCE sensor had good repeatability and reproducibility and could be used as a new sensor for detecting UA, XT and HX.
[0056] As shown in Table 1, in the actual sample detection, the recoveries of UA, XT and HX were 97.25-100.51%, 97.72-103.79% and 96.45-102.02%, respectively, and the corresponding RSD values were 2.80-3.84%, 2.31-4.27% and 2.50-5.01%, respectively. This result shows that the sensor of the present invention can be used for the determination of UA, XT and HX in actual samples.
[0057] Table 1 The application of the prepared FeS2 modified electrode in the determination of UA, XT and HX in actual fetal bovine serum samples
[0058]
[0059] Example 2
[0060] Collect discarded orange peels, wash them, take 1g of the inner pulp, chop it and put it into a polytetrafluoroethylene reactor, add 1mL H2SO4, 5mL SiO2 colloid, and 30ml ultrapure water to 30mL water, mix them evenly, add them into the polytetrafluoroethylene reactor, hydroheat at 453K for 12h, and dry the hydrothermal gel;
[0061] Under nitrogen protection, the dried gel was calcined in a tube furnace at 1173K for 4h (heating rate: 2K / min), the calcined material was etched three times with 10% HF, and then repeatedly washed with water and ammonia until neutral (pH=7.0), to obtain a biomass porous carbon material without metal sulfide modification;
[0062] 1 mg of the above-mentioned biomass porous carbon material without metal sulfide modification was dispersed in 1 mL of ultrapure water, and ultrasonicated for 10 minutes to form a uniformly dispersed and stable mixed solution. 5 μL of the mixed solution was drop-coated on the surface of the glassy carbon electrode and then dried in an infrared drying oven to obtain a porous carbon microsphere modified electrode PCMs / GCE.
[0063] Example 3
[0064] Collect discarded orange peels, wash them, take 1g of the inner pulp, chop it and put it into a polytetrafluoroethylene reactor, add 1mL H2SO4, 2g CoCl2, 5mL SiO2 colloid into 30mL water, and add 30ml ultrapure water to the polytetrafluoroethylene reactor, mix them evenly, add them into the polytetrafluoroethylene reactor, hydroheat them at 453K for 12h, and dry the hydrothermal gel;
[0065] Under nitrogen protection, the dried gel was calcined in a tube furnace at 1173K for 4h (heating rate: 2K / min), the calcined material was etched three times with 10% hydrofluoric acid, and then repeatedly washed with water and ammonia until neutral (pH=7.0), to obtain Co8S9 modified biomass grade porous carbon material;
[0066] 1 mg of the above-mentioned porous carbon material was weighed and dispersed in 1 mL of ultrapure water. Ultrasonic treatment was performed for 10 minutes to form a uniformly dispersed and stable mixed solution. 5 μL of the mixed solution was drop-coated on the surface of the glassy carbon electrode and then dried in an infrared drying oven to obtain the porous carbon microsphere modified electrode Co8S9 / PCMs / GCE.
[0067] Example 4
[0068] Collect discarded orange peels, wash them, take 1g of the inner pulp, chop it and put it into a polytetrafluoroethylene reactor, add 1mL H2SO4, 2g NiCl2, 5mL SiO2 colloid into 30mL water, and add 30ml ultrapure water to the polytetrafluoroethylene reactor after mixing evenly, and add it into the polytetrafluoroethylene reactor, hydroheat at 453K for 12h, and dry the hydrothermal gel;
[0069] Under nitrogen protection, the dried gel was calcined in a tube furnace at 1173K for 4h (heating rate: 2K / min), the calcined material was etched three times with 10% hydrofluoric acid, and then repeatedly washed with water and ammonia until neutral (pH=7.0), obtaining NiS2-modified biomass-grade porous carbon material;
[0070] Weigh 1 mg of the above-mentioned porous carbon material and disperse it in 1 mL of ultrapure water. Ultrasonicate for 10 minutes to form a uniformly dispersed and stable mixed solution. Take 5 μL of the mixed solution and drop it on the surface of the glassy carbon electrode, then dry it in an infrared drying oven to obtain the porous carbon microsphere modified electrode NiS2 / PCMs / GCE.
[0071] Example 5
[0072] Collect discarded orange peels, wash them, take 1g of the inner pulp, chop it and put it into a polytetrafluoroethylene reactor, add 1mL H2SO4, 2g CuCl2, 5mL SiO2 colloid into 30mL water, and add 30ml ultrapure water to the polytetrafluoroethylene reactor after mixing evenly, and add it into the polytetrafluoroethylene reactor, hydroheat at 453K for 12h, and dry the hydrothermal gel;
[0073] Under nitrogen protection, the dried gel was calcined in a tube furnace at 1173K for 4h (heating rate: 2K / min), the calcined material was etched three times with 10% hydrofluoric acid, and then repeatedly washed with water and ammonia until neutral (pH=7.0), to obtain Cu2S-modified biomass-grade porous carbon material;
[0074] 1 mg of the above-mentioned porous carbon material was weighed and dispersed in 1 mL of ultrapure water. Ultrasonic treatment was performed for 10 minutes to form a uniformly dispersed and stable mixed solution. 5 μL of the mixed solution was drop-coated on the surface of the glassy carbon electrode and then dried in an infrared drying oven to obtain a porous carbon microsphere modified electrode Cu2S / PCMs / GCE.
[0075] Example 6
[0076] Collect discarded orange peels, wash them, take 1g of the inner pulp, chop it and put it into a polytetrafluoroethylene reactor, add 1mL H2SO4, 2g ZnCl2, 5mL SiO2 colloid into 30mL water, and add 30ml ultrapure water, mix them evenly, add them into the polytetrafluoroethylene reactor, hydroheat at 453K for 12h, and dry the hydrothermal gel;
[0077] Under nitrogen protection, the dried gel was calcined in a tube furnace at 1173K for 4h (heating rate: 2K / min), the calcined material was etched three times with 10% hydrofluoric acid, and then repeatedly washed with water and ammonia until neutral (pH=7.0), to obtain ZnS-modified biomass-grade porous carbon material;
[0078] 1 mg of the above-mentioned porous carbon material was weighed and dispersed in 1 mL of ultrapure water. Ultrasonic treatment was performed for 10 minutes to form a uniformly dispersed and stable mixed solution. 5 μL of the mixed solution was drop-coated on the surface of the glassy carbon electrode and then dried in an infrared drying oven to obtain a porous carbon microsphere modified electrode ZnS / PCMs / GCE.
[0079] The electrochemical performance of the modified electrode in Examples 2-6 was tested as follows: Figure 1 The EIS curves of all electrodes in (A) are a slanted line (except the bare electrode), and there is almost no arc at high frequencies. Figure 1 The potential difference in (B) is smaller than that of the bare electrode, which indicates that the modified materials have good electron conductivity. However, the electron conductivity of all materials is smaller than that of FeS2 / PCMs material. Figure 2 In order to study the electrochemical cycling stability of the unmodified material, 5 mM [Fe(CN)6] 3- / 4- Cyclic voltammetry scans were performed continuously for 100 times in the solution, and the CV graphs of FeS2 / PCMs / GCE and ZnS / PCMs / GCE after 100 cycles showed almost no change. I p,a and I p,c The relative standard deviations (RSD) values were 0.31%, 0.17%, 0.70%, and 0.79%, respectively, indicating that FeS2 / PCMs / GCE and ZnS / PCMs / GCE have good electrochemical cycling stability and electrode stability.
[0080] In Examples 3-6, the porous carbon modified electrode performs electrochemical sensing detection under the detection object: Figure 3 In the figure, the response current of the sensors prepared by modified electrodes to UA, XT, and HX in 0.1M PBS (pH=2.0) is shown. It can be found that the response current of all modified electrodes is higher than that of the bare electrode, but significantly lower than the response current of FeS2 / PCMs / GCE, indicating that FeS2 / PCMs is superior to other materials in electrochemical sensing applications.
[0081] In summary, the modified electrode of the present invention is used for electrochemical detection, and the results show that it exhibits good electrocatalytic activity for three ATP metabolites (hypoxanthine (HX), xanthine (XT) and uric acid (UA)), and achieves efficient, sensitive, selective or simultaneous detection of XT, HX and UA, and the detection of XT exhibits a good oxidase-like reaction, and is successfully applied to the actual sample detection of three ATP metabolites in fetal bovine serum samples. At the same time, the modified electrode can effectively catalyze the oxidation of 3,3′,5,5′-tetramethylbenzylamine (TMB, a typical peroxidase substrate) by hydrogen peroxide or directly oxidize TMB, showing the dual enzyme characteristics of peroxidase and oxidase. The electrochemical sensor prepared by the present invention has the advantages of low preparation material cost, simple operation, rapid and efficient, high sensitivity, etc.
[0082] The above embodiments are merely preferred implementations of the present invention. Any simple modification, amendment and substitution of the above embodiments based on the technical essence of the present invention shall fall within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a FeS2 modified hierarchical porous carbon electrochemical sensor, characterized in that: The steps include: (1) Preparation of FeS2-modified hierarchical porous carbon materials The inner pulp of orange peel is used as carbon source, 98% H2SO4 is used as sulfur source, SiO2 colloid is used as silicon source, and FeCl3 is introduced as activator. After being uniformly mixed with ultrapure water, a hydrothermal reaction is carried out. The gel after the hydrothermal reaction was dried, calcined in a tube furnace under the protection of inert gas, etched three times with HF, and then repeatedly washed with water and ammonia until neutral, to obtain a FeS2-modified hierarchical porous carbon material; (2) Preparation of FeS2-modified hierarchical porous carbon-modified electrodes The FeS2-modified hierarchical porous carbon material prepared in step (1) is mixed with ultrapure water, and after ultrasonic dispersion, a suspension is formed. The suspension is drop-coated on a glassy carbon electrode and dried to obtain a FeS2-modified hierarchical porous carbon-modified electrode, which is a FeS2-modified hierarchical porous carbon electrochemical sensor, and electrochemical detection is performed in a phosphate buffer solution.
2. The method for preparing a FeS2 modified hierarchical porous carbon electrochemical sensor according to claim 1, characterized in that: Step (1), the amount ratio of the orange peel pulp, 98% H2SO4, SiO2 colloid and FeCl3 is 1g~5g: 0.5ml~1.5ml: 3ml~7ml: 1g~2g: 20ml~50ml.
3. The method for preparing a FeS2 modified hierarchical porous carbon electrochemical sensor according to claim 1, characterized in that: In step (1), the temperature of the hydrothermal reaction is 160°C to 200°C, and the time is 3h to 5h.
4. The method for preparing a FeS2 modified hierarchical porous carbon electrochemical sensor according to claim 1, characterized in that: In step (1), the calcination temperature in the tubular furnace is 800° C. to 1000° C., the heating rate is 3.75° C. / min, and the calcination time is 3.5 h to 4.5 h.
5. The method for preparing a FeS2 modified hierarchical porous carbon electrochemical sensor according to claim 1, characterized in that: In step (2), the inert gas is N2 and the concentration of HF is 10%wt.
6. The method for preparing a FeS2 modified hierarchical porous carbon electrochemical sensor according to claim 1, characterized in that: Step (2), the ratio of FeS2-modified hierarchical porous carbon material to ultrapure water is 1 mg / mL, and the amount of the suspension applied on the glassy carbon electrode is 5 μL.
7. The method for preparing a FeS2 modified hierarchical porous carbon electrochemical sensor according to claim 1, characterized in that: Step (2), using the prepared FeS2-modified hierarchical porous carbon-modified electrode as the working electrode, the platinum wire electrode as the counter electrode, and the reference electrode as a saturated calomel electrode to form a three-electrode system, using phosphate buffer solution as the electrolyte solution, and using differential pulse voltammetry to detect the contents of XT, HX, and UA in the test solution.
8. The method for preparing a FeS2 modified hierarchical porous carbon electrochemical sensor according to claim 1, characterized in that: In step (2), the pH of the phosphate buffer solution is 2 and the concentration is 0.1 mol / L.
9. Use of a FeS2-modified hierarchical porous carbon electrochemical sensor prepared by the preparation method according to any one of claims 1 to 8 in the selective or simultaneous detection of three ATP metabolites.
Citation Information
Patent Citations
Molecularly imprinted electrochemical sensor based on FeS2 / C / MQDs / GCE modified electrode and preparation method thereof
CN113552199A
Nanostructured fillers and carriers
US20020014182A1